Home Automation Controller with Security System - Abdul Rahim, Muhammad Khairul Anwar; Zahari, Muhammad Hamizan; Rahimi, Muhamad Faris Farhan; Md. Amin, Zulkarnain (Multidisciplinary Applied Research and Innovation, 2022)
The smart control system of electrical appliances in the home can generally give a very positive impact to the users that use this system. This is because they no longer bother to use a lot of their energy to do their daily activities such as turning on and off electrical appliances switches A good system is closely related to the safety of an individual, especially when they are in the place where they live. The Arduino-based system can increase the progress of the existing system and facilitate a user as well as increase the level of readiness. The project is wanted to create a prototype of an electrical hardware control system at home with an Arduino system concept. That also offer Bluetooth systems in the development of advanced systems for controlling electrical appliances at home. The system is controlled by two methods are a remote control and a smartphone connected via Bluetooth. The Arduino Nano is the heart of the control system to receive the program that is set. For security systems, the use of 4x4 Keypad as a means of access to the Door Knob Opener by move the Servo motor. The operation of this project will consist of two systems are smart home and security system. It has two control methods for smart homes are IR-remote and Bluetooth network.The idea is that the user must enter the correct password into the system so that the door does not open if the wrong password is entered. The low-cost method is intended to raise the standard of living in the home. It will act as a security system that can protect people from any incident that we don’t expect. Additional safety measures, such as cameras and motion detection sensors, can be readily added to the system.